Evaluation and management of shock in patients with COVID-19 - Fox, Steven; Vashisht, Rishik; Siuba, Matthew; Dugar, Siddharth (Cleveland Clinic Journal of Medicine, 2020)
Shock is common in critically ill patients with COVID-19, developing in up to 67% of patients in intensive care (5% to 10% overall) and is associated with high mortality. Optimal management requires prompt recognition with precise evaluation and differentiation. Correcting hypoperfusion and treating the underlying process are fundamental aspects of treatment. Undifferentiated shock may be treated initially with norepinephrine to optimize perfusion while additional evaluation is performed to categorize the shock pathophysiology. Physical examination, bedside echocardiography, hemodynamic monitoring, lactate and venous oxygen saturation are important components of the patient evaluation.